Extraction of phenolics from new oak casks during spirit maturation: impact on spirit colour. Issue 1 (20th January 2020) - Vivas, Nicolas; Vivas de Gaulejac, Nathalie; Bourden‐Nonier, Marie‐Françoise; Mouche, Claire; Rossy, Cybille
Abstract: The increase in colour and solubilisation of extract, polyphenols and ellagitannins were studied in wine spirit in new oak casks over a period of 23 years. Ellagitannins and oak colour were solubilised during the early years of maturation. After five years, the concentration of ellagitannins decreased markedly, while colour increased, although at a lower rate. Ellagitannins were oxidised into coloured polymers and hydrolysed into ellagic acid. The dry extract, containing polysaccharides, polyphenols and lignin, increased throughout maturation, growing quickly during the early years and slowly thereafter. In a model solution, ethanol exhibits a strong solvent effect. For higher concentrations (50% v/v and more), the extraction of colour was faster, and was typically dark yellow/brown with a red tone, attributable in part to the solubilisation of lignin and lignin by‐products. © 2020 The Institute of Brewing & Distilling